Frederick Douglass's Prophecies of Abolition: World Literature and the Black Romantic Man of Letters. Issue 4 (4th July 2018) - Sandler, Matt
ABSTRACT: Frederick Douglass's citations of British Romantic poets have recently attracted the attention of scholars working in two modes of Black Studies: transatlantic literary history and political theory. In this essay, I take as my point of departure that Douglass's Romanticism indicates his self-conception as a "man of letters" and his participation in the emergent discourse of "world literature." I show how Douglass reconceived these notions as modes of abolitionist practice. I contend that Douglass explored the generic variety of Romantic literature, and especially sought to exercise its prophetic capacity to address slavery. From the historical vantage of world literature, Douglass formulates a theory of abolition as structurally necessary to the function of liberalism. I conclude by suggesting that this premise helps contextualize the return of abolitionism in contemporary conversations about mass incarceration and police violence.